BRITISH FOREIGN SECRETARY’S ROLE AND INFLUENCE IN THE EXCLUSION OF GREECE AND TÜRKIYE FROM NATO, 1948–1949 (Journal of International Studies, 2023)
When NATO was created on 4 April 1949 by the United States, Britain, Canada, and several Western European countries with the aim tocontain the Soviet Union’s expansion of power, it was rather peculiar that Greece and Türkiye were excluded, while their Mediterranean neighbour, Italy, was included in this new military organisation. As Greece suffered from the communist insurgents in the Greek Civil War (1946–1949), and Türkiye was unceasingly under Soviet military and diplomatic threat over the provinces of Kars and Ardahan and the Turkish Straits settlements (1946–1953), both seemingly had valid reasons for being included in NATO. However, Britain, one of the renowned founding members of NATO, determinedly repudiated to invite Greece and Türkiye to join NATO. This paper analyses the reasons for Britain to deny these countries NATO membership. The existing literature on this exclusion subject argues that the geographical location and the forthcoming Mediterranean Pact were two apparent causes that influenced Britain to reject Greece and Türkiye’s NATO membership. This paper however, investigates other rejection reasons that have yet to be studied by previous scholars. This paper offers an analysis of Britain’s objections to Greece and Türkiye’s NATO membership during NATO’s creation years through the study of British primary historical records. The finding shows that Foreign Secretary Ernest Bevin was eager to have NATO promptly formed, and he believed the proposal for Greece and Türkiye’s inclusion in NATO would hamper this aim, since these two countries were in a dispute over Cyprus. Bevin reckoned that the bitter relationship between Greece and Türkiye over Cyprus would alarm the delegations, hence prolonging the discussions that would lead to further postponement of NATO’s ratification. Thus, Bevin’s démarche was not to propose the inclusion of Greece and Türkiye in NATO at the time.